Digital transformation strategies for enhancing transparency and efficiency in public asset management systems - Ady Setiawan; Robert Marbun; Hendri Setiadi; Scherly Hansopaheluwakan; Wahyuddin Albra (Indonesian Indovisi Institute, 2026)
Digital transformation has become a strategic priority for improving governance, accountability, and operational effectiveness in the public sector. However, evidence on its role in enhancing transparency and efficiency in public asset management remains fragmented. This study aimed to synthesize digital transformation strategies for improving public asset management. A qualitative Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using 52 peer-reviewed studies published between 2015 and 2025. The included studies were critically appraised, and thematic coding achieved substantial inter-rater reliability (Cohen's κ = 0.84). The analysis identified five strategic dimensions: digital infrastructure, integrated asset information systems, data governance and interoperability, transparency enhancement, and efficiency enhancement. Integrated asset information systems and data governance emerged as the strongest enablers of transparency and operational efficiency. The proposed Digital Transformation Strategy Framework integrates technological, governance, institutional, transparency, and efficiency dimensions into a unified model for public asset management. These findings provide practical and theoretical guidance for strengthening transparency, efficiency, accountability, and public value creation.